2016
DOI: 10.4999/uhod.161317
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Attitudes Among Patients with Cancer Receiving Chemotherapy.

Abstract: Immunization against vaccine preventable diseases is an essential but mostly overlooked issue in oncology practice. We aimed to investigate the utilization of adult immunization recommendations and the perception of the patients with cancer receiving chemotherapy on immunization. A 15-item questionnaire about immunization in adults with cancer diagnosis was administered to patients with various cancers treated in daycare chemotherapy unit of Hacettepe University Cancer Institute. Total of 229 patients complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Another study that included patients over 75 years with a diagnosis of cancer has shown the rate of vaccination with pneumococcal vaccine as 5.5% [ 8 ]. Similar vaccination rates for the pneumococcal vaccine have been reported as 4.2–7.4% in patients with cancer in Turkey [ 9 , 10 ].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Another study that included patients over 75 years with a diagnosis of cancer has shown the rate of vaccination with pneumococcal vaccine as 5.5% [ 8 ]. Similar vaccination rates for the pneumococcal vaccine have been reported as 4.2–7.4% in patients with cancer in Turkey [ 9 , 10 ].…”
Section: Introductionsupporting
confidence: 77%
“…The pneumococcal vaccination rate was previously found to be 7.4% in cancer patients who attend a medical oncology clinic in Turkey [ 9 ]. Therefore, this study considered a twofold increase in vaccination rates for the target (15% increase in vaccination rates compared to the control group).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, ICP with comorbidities in their medical history tend to have a higher uptake in four [38,39,42,54] out of seven studies. One study reported a negative association [42] and two found no significant difference [33,52]. All five papers that included vaccination history (for the same or another vaccination), concluded that there was a positive association between vaccination uptake in the past and current uptake [34,43,46,47,52].…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…Furthermore, it was shown in this study that physicians are more likely to recommend the pneumococcal vaccine, whereas nurses are more likely to recommend the diphtheria-tetanus vaccine for patients with cancer. It has been known that the recommendation of vaccines by healthcare professionals, particularly by physicians, affects patient's actual vaccination behavior [20,21]. Likewise, antivaccine attitudes of patients affect healthcare professionals' attitudes toward the recommendation of vaccines to their patients which was highlighted by this study.…”
Section: Discussionmentioning
confidence: 72%